Techniques Used in Teaching Reading Skill in Senior High School: A Systematic Literature Review - Raditya, Thea; Sutiono, Cayandrawati; Arapah, Elvina (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2024)
English teachers have to use the best reading teaching techniques to make their students improve their reading skills to understand an English text or the written language. Since reading is not an easy skill to master, teachers need to choose appropriate reading techniques that help the students improve their reading skills to comprehend the English text they read. This research aims to discover the techniques used to teach reading skills in senior high school classes. The techniques are explored through the research articles written by previous researchers on this topic. This study employed a systematic analysis method that identifies existing articles that are available online. The research reviewed 20 articles on the research topic, which were collected from Google Scholar. This research highlighted four teaching techniques frequently mentioned and suggested as effective in teaching reading skills. They were: Think-Pair-Share, reciprocal teaching, mind mapping, and Question-Answer Relationship (QAR). These techniques have been proven effective in improving students’ reading comprehension. These techniques are, of course, not without shortcomings. Thus, teachers need to pay attention to the situation of their classes in choosing appropriate techniques, especially in teaching reading skills. Implementing the appropriate techniques brings instruction to life while encouraging students to actively engage in class.